Technology with a Human Face: Reimagining Progress through Universal Ethical Principles - Tarakanta Sahoo; Priyanka Priyadarshini (International Journal of Behavioral Sciences, 2026)
Technological progression is mostly considered as a tool of human evolution. In this digital era, however, quick novelty has revealed complex ethical gaps in the modelling and implement of technology. Technologies namely artificial intelligence, algorithmic systems, and digital surveillance progressively effect social life, economic activity, and political decision-making. While these technologies provide proficiency and progress, they also advance moral concerns connected to discretion, disparity, liability, and human dignity. The technique seriously observes the leading technology-run knowledge of development and queries its moral suitability. The work propounds a logical and normative method to reveal the impression of expertise with a human face. This perception underscores the requirement to normalise scientific advancement in global moral values. Combining human rights dissertation along with universal moral outlines, this very work claims that knowledge itself is not worthy, but is guided by communal conventions, power constructions, and human selections. The moment moral reflection is unnoticed, technology can strengthen inequality and fade distinct independence. In order to converge on ethics namely human pride, righteousness, transparency, independence, and sustainability, the work re-considered advancement as a morally directed course. It settles that decent values should be united with technological novelty. This combination is needed to certify that technology assists civilisation and cares comprehensive and justifiable growth.
Keywords: Humanity; Justice; Sustainability; ethics; progress; technology